The role of insulin detemir in overweight type 2 diabetes management - Yared N Demssie; Naveed Younis; Handrean Soran (Vascular Health and Risk Management, 2009)
Yared N Demssie1, Naveed Younis2, Handrean Soran31Department of Diabetes and Endocrinology, Salford Royal Foundation NHS Trust, Salford, UK; 2Department of Medicine, University Hospital South Manchester Foundation NHS Trust, Wythenshawe, Manchester, UK; 3University Department of Medicine, Central Manchester and Manchester Children’s NHS Foundation Trust, Manchester, UKAbstract: The recent evidence-based shift towards an algorithm of early initiation and aggressive titration of insulin therapy in the management of type 2 diabetes requires the use of an effective insulin formulation that is both safe and acceptable to patients and physicians alike. The advent of the long-acting insulin analogues, insulin detemir and glargine, in the last decade has revolutionized insulin therapy in type 2 diabetes. Their unique pharmacokinetic and pharmacodynamic properties have offered tangible advantage over the conventional intermediate and long-acting insulin preparations in terms of improving glucose control as well as reducing risk of hypoglycemia and weight gain. This review focuses on the pharmacodynamic properties of the long-acting insulin analogue detemir, the outcome of studies on its relative efficacy and safety as well as its proposed place in the management of type 2 diabetes.Keywords: insulin detemir, type 2 diabetes, overweight